How can effective dialogue be established between researchers and policy makers on climate change adaptation in Mali - Sogoba, Bougouna; Ba, Allassane; Zougmoré, Robert B.; Samaké, Ouodiouma B. (2014)
This briefing note summarizes the main findings of the study, conducted as part of the national platform of science-policy dialogue on climate change, agriculture and food security, or CASA C-platform created in 2012 on the importance of the researchers and decision makers dialogue and possible avenues for improvement. These findings come from the interview of 17 key institutions in adapting to climate change, collectively selected from among the members of the National Climate Change Committee of Mali.